Microservice Architectures for Secure Digital Wallet Integrations - Garg, Varun; Khan, Shakeb (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
In the era of rapid digital transformation, digital wallets have emerged as a cornerstone of modern financial ecosystems, enabling seamless, secure, and efficient payment solutions. This paper explores the role of microservice architectures in facilitating secure integrations of digital wallets within diverse application environments. Traditional monolithic architectures often struggle to meet the scalability, flexibility, and security demands of digital wallets. Microservices, with their modular and decentralized approach, offer significant advantages by enabling the independent deployment and scaling of services, as well as fostering a culture of agility in development. The study delves into the architectural principles of microservices, highlighting their capacity to enhance security through fine-grained authorization, API gateway layers, and zero-trust frameworks. Key challenges such as inter-service communication, data consistency, and compliance with financial regulations are analyzed, along with strategies to mitigate these risks through robust design patterns. Case studies are presented to illustrate successful implementations of microservice-based digital wallet integrations, emphasizing their impact on transaction security, user authentication, and fraud prevention. The findings demonstrate that adopting microservice architectures for digital wallet integrations can significantly improve resilience, scalability, and the overall security posture of payment ecosystems. This research provides actionable insights for architects and developers aiming to build future-ready financial platforms that prioritize security without compromising user experience.